2010
DOI: 10.1021/ja106436y
|View full text |Cite
|
Sign up to set email alerts
|

Large Polyoxotitanate Clusters: Well-Defined Models for Pure-Phase TiO2 Structures and Surfaces

Abstract: Careful control of the temperature and duration of the reaction between titanium tert-butoxide and acetic acid leads to the formation of new polyoxotitanate clusters with 14, 18, and 28 Ti atoms. They are considered intermediates in the growth of Ti/O nanoclusters of increasing size. The Ti(28) cluster is the largest crystallized to date. UV/vis spectroscopy on this cluster reveals that the optical band gap is blue-shifted with respect to a cluster containing only 17 titanium atoms indicating that the optical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
169
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(173 citation statements)
references
References 20 publications
4
169
0
Order By: Relevance
“…350 nm for both). [33,34] It can therefore be concluded that this series of cobalt(II)-doped cages exhibits a similar trend in optical behavior as observed in cobalt(II)-doped bulk and nanoparticulate TiO 2 [13-18, 26, 27] and that there is a trend towards increased red-shift in the absorption edge with increased cage size. However, there is clearly also a very strong structurally dependent element to the absorption edge behavior, as seen in 4 which exhibits a large red-shift in the absorption edge (ca.…”
supporting
confidence: 56%
“…350 nm for both). [33,34] It can therefore be concluded that this series of cobalt(II)-doped cages exhibits a similar trend in optical behavior as observed in cobalt(II)-doped bulk and nanoparticulate TiO 2 [13-18, 26, 27] and that there is a trend towards increased red-shift in the absorption edge with increased cage size. However, there is clearly also a very strong structurally dependent element to the absorption edge behavior, as seen in 4 which exhibits a large red-shift in the absorption edge (ca.…”
supporting
confidence: 56%
“…[16][17][18] Along this line, polyoxo-titanium clusters (PTCs) have been attracting much research attention in recent years, because they possess well-defined structures and can be used as reactivity model compounds of TiO 2 nanoparticles. [19][20][21][22][23][24][25] Another major advantage of PTCs is that they can be easily functionalized by organic ligands. 26 In the course of our research on titanium-oxo clusters, recently, we successfully applied a variety of bridging ligands to organize the 0D {Ti 6 3 ) is observed that has been reported earlier in many molecular clusters ( Fig.…”
mentioning
confidence: 99%
“…Great attentions have been paid on titanium-oxo-clusters (TOCs) because of their use as the model compounds of the nanoscale titanium oxide [1][2][3][4] and offering the opportunity to understand the information in terms of both atomic structure and chemical reactivity [5][6][7][8][9][10]. A large number of titanium-oxo-clusters based on Electronic supplementary material The online version of this article (doi:10.1007/s10876-015-0960-0) contains supplementary material, which is available to authorized users.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of titanium-oxo-clusters based on Electronic supplementary material The online version of this article (doi:10.1007/s10876-015-0960-0) contains supplementary material, which is available to authorized users. alkoxides and carboxylate ligands have been described [11][12][13], including the Ti 28 cluster [Ti 28 O 40 (O t Bu) 20 (OOAc) 12 ], a larger carboxylate-substituted TOC synthesized recently [10]. Among them, however, the TOCs constituted with dicarboxylate are still rare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation